Judgments service History - Menoncello, Aline Michelini [UNESP] (Univ Federal Ouro Preto, Dept Historia, 2016)
By going through the records of the Brazilian Historical and Geographical Institute Magazine (RIHGB) between 1901 and 1921, I investigated the participation of Pedro Augusto Carneiro Lessa (1859-1921), Minister of the Supreme Court. Thus I asked myself: who works for History in the History Institute, the judge Pedro Lessa or the historian Pedro Lessa? This question will be answered from the questioning of the category author offered by the French philosopher Michel Foucault and analysis of the texts signed by Pedro Lessa: the evaluation in History Commission, the study for the centenary of the birth of Francisco Adolfo de Varnhagen and the Final Report to decide the commemorative date of the Confederation of the Equator.
Keywords: History writing; Discourse; History of Historiography